Factors Influencing Coffee Farmers' Income in Kisam Tinggi District, Ogan Komering Ulu (OKU) Selatan Regency: A Case Study of Simpang Empat Village - Sonia Anjelica; Muhammad Huseini (Cita konsultindo, 2024)
Coffee farming is a key agricultural activity in Kisam Tinggi District, especially in Simpang Empat Village. This study aims to identify the factors influencing coffee farmers' income in Kisam Tinggi District, Ogan Komering Ulu (OKU) Selatan Regency. The research employs a quantitative approach, with data processed according to the relevant model. Data sources include questionnaires and structured interviews, and the analysis is performed using classical assumption tests, multiple linear regression, and hypothesis testing with Eviews 10 software. The results indicate that, simultaneously, the independent variables have a significant and positive effect on the dependent variable. Additionally, individually, land area, labor, fertilizer costs, and pesticide costs significantly and positively impact farmers' income.